Decomposition of form surfaces for planning of machining - Beno, Jozef; Stahovec, Jozef; Izol, Peter; Tomas, Miroslav (Manufacturing Technology Journal, 2012)
Paper deals with manufacturability of form surfaces produced by 3D milling operations. Based on decomposition of form surfaces, which are designed by CAD, virtual elementary operations of milling form surfaces are presented. Some typical engineering components with form surfaces were designed to analyse their features. Forms surfaces are classified to give review of dimensionless basic shapes. Review of milling strategies is introduced to select planning of machining of surfaces taken from virtual components. A representative component was analysed in order to obtain overall length of tool paths related to the elementary surfaces. Examples of process planning of elementary surfaces which conform to their classification are discussed. Combination of milling strategies to achieve desired surface finish is introduced.
Keywords: Form surface; CAM; SolidCAM; virtual representation; process planning